2014
DOI: 10.1007/s00467-014-2992-3
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mass and diastolic function in obese children and adolescents

Abstract: Early markers of cardiac disease including hypertrophy and diastolic dysfunction of the left ventricle are present in youths with obesity prior to the development of sustained hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
2
28
0
1
Order By: Relevance
“…While in adults the correlation between obesity and diastolic function is well established [14,51], the studies on this issue published up to now in children are few. In agreement with our data, most of these studies show initial signs of impaired left ventricular relaxation in weight-excess children as compared to normal-weight peers [16][17][18][19][20]52]. It is interesting to note that in our population, waist circumference values are independently associated to a worsening in diastolic function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While in adults the correlation between obesity and diastolic function is well established [14,51], the studies on this issue published up to now in children are few. In agreement with our data, most of these studies show initial signs of impaired left ventricular relaxation in weight-excess children as compared to normal-weight peers [16][17][18][19][20]52]. It is interesting to note that in our population, waist circumference values are independently associated to a worsening in diastolic function.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have addressed the left ventricular geometric patterns in children. Children with hypertension associated with obesity have the highest prevalence of cardiac geometry alterations, in particular, a great prevalence of both concentric and eccentric hypertrophy has been observed [20,52,57]. Moreover, Śladowska-Kozłowska et al [58] observed that eccentric hypertrophy was the most frequent pattern of left ventricular remodeling in adolescents with essential hypertension and central obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Obesity is an independent predictor of left ventricular diastolic dysfunction, in all age groups,77,78 predisposing to alterations in LA size, which is a known risk factor for the development of AF 79,80. Additionally, pericardial fat has been associated with the presence, symptom burden, chronicity, and recurrence of AF 81,82…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…Furthermore, obesity has been strongly linked to LA size 13,14 , as well as electrostructural remodeling, which has been associated with spontaneous and more persistent AF 15 . Additionally, data suggests that obesity is an independent predictor of left ventricular (LV) diastolic dysfunction, in all age groups from children as early as age 9 years to the elderly 16,17,18 , which is a known risk factor for the development of AF 19,20 .…”
Section: Obesitymentioning
confidence: 99%
“…A meta-analysis of 16 25 . Importantly, a large, prospective, community-based observational cohort study demonstrated a 4% increase in AF risk per 1-unit increase in body mass index (BMI) in men (95% CI, 1%-7%; P = .02) and in women (95% CI, 1%-7%; P = .009) 26 .…”
Section: Obesitymentioning
confidence: 99%